A methodological framework for the hydrological model selection process in water resource management projects. (4th August 2021) - Ghonchepour, Diba; Sadoddin, Amir; Bahremand, Abdolreza; Croke, Barry; Jakeman, Anthony; Salmanmahiny, Abdolrassoul
Abstract: This study aims to present a process for hydrological model exploration for selecting an appropriate model compatible with the modeling objectives. The process consists of three stages: (1) initial choice based on the modeling objectives; (2) model selection based on intercomparison among underlying conceptualizations of the models; and (3) final model selection based on influencing criteria such as availability of the model software and documentation, and availability of appropriate data. As an applied example, the process was used to find an appropriate model for a project to evaluate water supply and demand under climate and land use change scenarios in the Gorgan‐rud River Basin, Iran. The criteria affecting the final choice of a hydrological model were classified into three categories: (1) criteria related to the model, (2) criteria related to the model user, and (3) criteria related to the study area. Recommendations for resource managers: It is vital to simulate the hydrological conditions on an appropriate temporal and spatial scale useful for management purposes. The simulation resolution should be consistent with the resource management requirements. The simulation resolution depends on modeling objectives. The criteria related to data availability, the model user and those related to the study area are among the main factors affecting the final choice of a hydrological model.